Exhaled breath particles as a diagnostic tool for bronchiolitis obliterans syndrome in lung transplant recipients: a longitudinal study - Gu, Runchuan; Bodén, Embla; Lindstedt, Sandra; Olm, Franziska (Frontiers in Transplantation, 2025)
BackgroundLong-term survival after lung transplantation is significantly shorter compared with other solid organ transplantations. Chronic lung allograft dysfunction (CLAD), including bronchiolitis obliterans syndrome (BOS), remains the major barrier to survival. CLAD is diagnosed according to ISHLT's guidelines: a 20% drop in FEV1 using spirometry for CLAD grade 1. Given the difficulties of confounders using spirometry, other methods for precise diagnostics are being explored. Exhaled breath particles (EBP) measured as particle flow rate (PFR) from the airways have been explored as a potential method to diagnose lung injury in preclinical and clinical settings of acute respiratory distress syndrome (ARDS) and primary graft dysfunction (PGD). In fact, PFR has been shown to indicate early signs of lung injury in both ARDS and PGD settings. In the present study, we explored whether PFR could be used as a marker for BOS.MethodsLung transplant patients with different BOS grades were included. All patients were in stable condition without ongoing infections and >2 years posttransplantation. PFR (in particles per liter) was measured using a Particles in Exhaled Air (PExA) 2.0 device (PExA, Gothenburg, Sweden), containing an optical particle counter, at the start of the study and then 1 year out, in total two time points (0 and 1 year). Particles in the diameter range of 0.41–4.55 µm were measured.ResultsAt both the start of the study and 1 year out, patients with BOS grade 0 had significantly higher PFR than patients with BOS grades 2–3. During the study period, patients who progressed in their BOS grade all expressed lower PFR as they progressed in BOS grade, while patients who remained stable in BOS grade did not. The particle distribution between the different BOS grades had a similar pattern; however, it significantly decreased PFR with severity in the BOS grade.ConclusionsEBP expressed as PFR could be used to distinguish severity in BOS grade and could be used to follow the progression of BOS over time. PFR could be used as a new diagnostic tool for BOS and to follow the development of lung function over time.